1989
DOI: 10.3382/ps.0680335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Assessment of the Behavior of White Leghorn Type Pullets in an Open Field

Abstract: Open field tests were carried out using 17-wk-old pullets derived from two commercial White Leghorn type stocks of males bred to White Leghorn type females from a stock kept at the University of Guelph. Behavioural differences both between and within stocks were investigated, and the heritabilities of the behavioral variables were calculated. The offspring of male parental Stock 1 took longer to manifest pecking behavior than those of male parental Stock 2, and also made less use of the areas of the open field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The genetic stocks derived from the two male parental stocks will be referred to as MPS1 and MPS2. Rearing and management in dam family groups within hatches have been described in Webster and Hurnik (1989).…”
Section: Birds Housing and Managementmentioning
confidence: 99%
“…The genetic stocks derived from the two male parental stocks will be referred to as MPS1 and MPS2. Rearing and management in dam family groups within hatches have been described in Webster and Hurnik (1989).…”
Section: Birds Housing and Managementmentioning
confidence: 99%
“…Although the open field test was originally developed for comparative psychology in rodents, nowadays it can be used to determine welfare in farm animals, such as pigs (Mormede at al., 1994), chickens (Webster & Hurnik, 1989), quails (Jones at al., 1991), sheep (Moberg et al ., 1980) and cattle (Mullens et al ., 2006). …”
Section: Open Field Test: Equipment and Procedures Of Testingmentioning
confidence: 99%
“…Common fear-avoidance is associated with escaping, jumping and flight behaviours in an open field test (Melik et al 2006;O'Brien and Sutherland 2007). Estimates of heritability (h 2 ) in open field behaviours have been observed in several studies and found to range from 0.08 to 0.49 for overall locomotion and from 0.06 to 0.10 for defecation (Boyer et al 1970;Faure 1981;Webster and Hurnik 1989). Ambulation in the open field is also heritable (Forkman et al 2007).…”
Section: Introductionmentioning
confidence: 99%